Inflammation-Related MicroRNAs Are Associated with Plaque Stability Calculated by IVUS in Coronary Heart Disease Patients. (1st December 2019) - Zhu, Guo-fu; Chu, Tianshu; Ruan, Zhimin; Zhang, Mingguo; Zhou, Mingli; Zhang, Qian; Zhang, Ran; Wu, Liyong
Abstract : Objectives . This study aimed to investigate the association between inflammation-related microRNAs (miR-21, 146a, 155) and the plaque stability in coronary artery disease patients. Methods . The expression of miR-21, 146a, and 155 was measured by real-time PCR in 310 consecutive patients. The level of hs-CRP, IL-6, and IL-8 was measured by ELISA. The plaque stability of coronary stenotic lesions was evaluated with intravascular ultrasound (IVUS). Results . (1) The levels of hs-CRP, IL-6, and IL-8 were significantly increased in the UAP and AMI groups compared with the CPS group (P < 0.01 ). (2) The expression of miR-21 and miR-146a in peripheral blood mononuclear cells (PBMCs) and plasma was significantly higher in CAD patients compared with non-CAD patients, whereas the miR-155 expression in PBMCs and plasma was significantly lower in patients with CAD. (3) The miR-21 expression in PBMCs was higher in UAP and AMI groups compared with CPS group. The miR-146a expression in PBMCs was higher in SAP, UAP, and AMI groups than in CPS group. Although the level of miR-155 in PBMCs was lower in SAP, UAP, and AMI groups than in CPS group. The expression patterns of miR-21, miR-146a, and miR-155 in plasma were consistent with those of PBMCs. (4) The expressions of miR-21 and miR-146a in PBMCs and plasma were significantly higher in the vulnerable plaque group than those in stable plaque group. While miR-155 in PBMCs and plasma was significantly lower in vulnerable plaque group compared with stable plaque group. (5) The levels of miR-21 and miR-146a in PBMCs and plasma were significantly higher in soft plaque group than in fibrous plaque group and calcified plaque group. However, miR-155 in PBMCs and plasma was significantly lower in soft plaque group. Conclusions . The expression of miR-21 and miR-146a are associated with the plaque stability in coronary stenotic lesions, whereas miR-155 expression is inversely associated with the plaque stability.